How multilevel governance affects the clash of capitalisms - Helen Callaghan (Max Planck Institute for the Study of Societies, 2008)
This article challenges the methodological nationalism of the convergence debate by arguing that multilevel governance destabilizes the coalitions thought to underpin liberal and coordinated varieties of capitalism. Existing efforts to explain how coherent production regimes emerge and persist assume that some dominant social bloc ensures coherence by imposing its interests across all relevant regulatory subspheres. This assumption is not tenable in systems of multilevel governance. Three features of multilevel governance diminish the scope for a uniform social bloc to ensure a tight coupling of complementary regulations. First, the strategic opportunities for playing multilevel games vary across regulatory subspheres. Second, willingness to exploit these opportunities varies, because the transnational scope of legislation adds a constrain-competitor dimension to actors' decision-making that may either strengthen or weaken interest group cohesion. Third, the institutional set-up at the supranational level of Europe's multilevel polity multiplies alignment options. To illustrate these claims, the article draws on case studies of EU company law initiatives concerning takeovers and worker participation.
Keywords: 300; Politische Entscheidung; Governance-Ansatz; EU-Politik; Kapitalismus; Systemvergleich; EU-Staaten